Penerapan Metode Istinbath Ahkam dalam Mengembangkan Asuransi Syariah: Studi tentang Prinsip dan Praktik - Azijah, Siti Amalia; Nuraeni, Neni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the application of the istinbath ahkam method in the development of Islamic insurance (takaful), focusing on principles and practices aligned with Islamic law. The istinbath ahkam method is used to derive and determine rulings from Sharia sources such as the Qur’an, Hadith, ijma’, and qiyas, as well as supplementary sources. In the context of Islamic insurance, this method plays a crucial role in ensuring that products and contracts are free from elements of gharar (uncertainty), maisir (gambling), and riba (interest). This article elaborates on the basic concept of the istinbath method, the main principles of Islamic insurance, and its implementation in regulations and Islamic insurance products in Indonesia. The study finds that applying the istinbath method not only ensures Sharia compliance but also provides a foundation for product innovation aligned with the objectives of Sharia (maqashid al-shariah), enabling Islamic insurance to grow sustainably and remain competitive in the modern market.